The Relationship between Motivation for Achievement and Reasoning with Teacher Work Performance - Nur, Farihin; Syamsi, Atikah (Pascasarjana IAIN Kudus, 2022)
The purpose of this study is to reveal whether or not there is a relationship and the strong relationship between teacher achievement motivation and teacher work performance, to reveal whether or not there is a relationship and the strong relationship between teacher reasoning abilities and teacher work performance. The population in this study were all teachers at MA in Indramayu district totaling 155 respondents with 30 respondents. The results showed that there was a positive relationship between achievement motivation and teacher work performance. Both go hand in hand, meaning that the higher the achievement motivation, the higher the teacher's work performance. Thus, the contribution of this study includes nopositive relationship between reasoning ability and teacher work performance. There is a positive relationship between achievement motivation and reasoning ability with teacher work achievement. The two independent variables go hand in hand with the dependent variable, the higher the teacher's work performance. Hubungan Motivasi Berprestasi dan Penalaran dengan Prestasi Kerja Guru. Tujuan penelitian ini adalah untuk mengungkapkan ada atau tidaknya sebuah hubungan, dan seberapa kuat hubungan antara motivasi prestasi guru dengan prestasi kerja guru, untuk mengungkapkan ada hubungan atau tidaknya dan hubungan yang kuat antara kemampuan penalaran guru dengan prestasi kerja guru. Populasi dalam penelitian ini adalah seluruh guru di MA di kabupaten Indramayu yang berjumlah 155 responden dengan 30 responden. Hasil penelitian menunjukkan bahwa terdapat hubungan positif antara motivasi berprestasi dengan prestasi kerja guru. Keduanya berjalan beriringan, artinya semakin tinggi motivasi berprestasi, semakin tinggi prestasi kerja guru. Dengan demikian kontribusi penelitian ini antara lain tidak ada hubungan positif antara kemampuan penalaran dengan prestasi kerja guru. Terdapat hubungan positif antara motivasi prestasi dan kemampuan penalaran dengan prestasi kerja guru. Kedua variabel independen berjalan beriringan dengan variabel dependen, semakin tinggi prestasi kerja guru.